Neurolysis of the Long Thoracic Nerve for Scapular Winging due to Isolated Serratus Anterior Palsy: Early and Midterm Results in 29 Patients - Ng, Chye Yew; Griffiths, Emmet John; Wu, Feiran (Journal of Hand and Microsurgery, 2023)
Objective This study aimed to report our surgical outcomes of thoracic long thoracic nerve (LTN) decompression in patients with isolated LTN palsy, using a clinical scoring system designed to facilitate the grading of scapular winging severity.Methods This was a retrospective review of patients who had undergone decompression and neurolysis of the LTN for scapular winging. Each patient underwent needle electromyography of the serratus anterior for confirmation of diagnosis and were refractory to a minimum of 6 months of nonoperative management. Preoperatively and at final follow-up, shoulder range of motion and the Wrightington Winging Score (WWS) was used to objectively grade the dynamic and static components of winging.Results Between 2014 and 2020, 29 patients who underwent thoracic neurolysis for scapular winging were analyzed. These were 16 males and 13 females with a mean age of 37 years. The injury mechanism was due to trauma in 19 cases and neuralgic amyotrophy in 10. The median duration between winging onset and surgery was 30 months. There were significant improvements in mean active shoulder abduction and forward flexion. Winging was noticeably improved in 22 patients. At presentation, the median WWS was 3, which improved to 1 at final follow-up.Conclusion In patients with isolated LTN palsy causing persistent scapular winging which is not responsive to conservative treatment, neurolysis of the thoracic portion of the LTN can be considered.Level of Evidence: IV.
Keywords: dyskinesis; long thoracic nerve; nerve; nerve decompression; neuralgic amyotrophy; scapular winging; serratus anterior